Appraising Crumb Tire Ash as a Partial Cement Substitute in Concrete for Sustainable Construction - , O.A. Olaniyi, A.K. Oyelami (Archives of Current Research International, 2025)
The increasing demand for sustainable construction materials has driven research into alternative cementitious materials. This study investigates the use of Crumb Tire Ash (CTA) as a partial cement replacement in Concrete to evaluate its effects on workability and compressive strength. CTA was produced by burning and milling waste tire rubber into fine ash. Laboratory tests, including specific gravity, sieve analysis, slump flow, V-funnel, and L-box tests, were conducted to assess the physical and rheological properties of the concrete. The mix design included cement replacement levels of 0%, 5%, 10%, and 15% CTA, with samples cured for 7, 21, and 28 days. The results showed that CTA-modified Concrete met fresh concrete requirements, but an increase in CTA content negatively impacted filling and passing ability. The density of the concrete increased with age and replacement percentage, remaining within the range for normal-weight concrete. Compressive strength results at 7 days for 0%, 5%, 10%, and 15% CTA were 11.04 N/mm², 11.47 N/mm², 12.67 N/mm², and 12.46 N/mm², respectively. At 21 days, the strengths were 15.09 N/mm², 16.03 N/mm², 17.07 N/mm², and 16.63 N/mm², while at 28 days, they were 21.18 N/mm², 21.33 N/mm², 21.57 N/mm², and 20.04 N/mm², respectively. For splitting tensile strength, results at 7 days were 13.30 N/mm², 14.19 N/mm², 14.49 N/mm², and 14.17 N/mm², while at 28 days, they were 22.98 N/mm², 22.83 N/mm², 23.57 N/mm², and 22.54 N/mm², respectively. The study found that 10% CTA replacement yielded the highest compressive and tensile strengths, demonstrating an optimum blend for improved mechanical properties. This research contributes to sustainable construction by repurposing waste tires as a cement substitute, reducing cement consumption, and mitigating environmental hazards. However, higher CTA replacement negatively affected workability and strength, indicating a limit to its usage in structural applications.